Early persistent hyperparathyroidism post‐renal transplantation as a predictor of worse graft function and mortality after transplantation. Issue 11 (5th October 2020) - Isakov, Ofer; Ghinea, Ronen; Beckerman, Pazit; Mor, Eytan; Riella, Leonardo V.; Hod, Tammy
Abstract: Background: Persistent hyperparathyroidism (pHPT) is frequently seen after transplantation contributing to post‐transplant complications. Methods: We conducted a retrospective single center analysis to explore the relationship of early pHPT and long‐term allograft outcome. Patients were divided into high (N = 153) and low (N = 252) PTH groups based on serum parathyroid hormone (PTH) level 3 months post‐transplant (PTH ≥ 150 and < 150 pg/mL, respectively). Results: High PTH was found to be an independent predictor for reduced kidney allograft function up to 3 years post‐transplant. eGFR decreased by 11.4 mL/min ( P  < .001) and the odds of having an eGFR < 60 mL/min 3 years post‐transplant were sixfold higher ( P  < .01) in the high compared to the low PTH group. Subgroup analysis based on eGFR 1 year post‐transplant, presence of slow graft function (SGF), and transplant type revealed similar results. High PTH three months post‐transplant was also independently associated with an increased risk for overall mortality and for death with a functioning graft ( P  < .05). Conclusions: pHPT three months post‐renal transplantation is an independent predictor for a worse allograft function up to 3 years post‐transplant and a risk factor for mortality. This relationship remains statistically significant after accounting for baseline allograft function, presence of SGF and serum mineral levels abnormalities.